Increased astrocytic ATP release results in enhanced excitability of the hippocampus. Issue 2 (27th September 2012) - Lee, Hae Ung; Yamazaki, Yoshihiko; Tanaka, Kenji F.; Furuya, Kishio; Sokabe, Masahiro; Hida, Hideki; Takao, Keizo; Miyakawa, Tsuyoshi; Fujii, Satoshi; Ikenaka, Kazuhiro
Abstract Astrocytes, a major subtype of glia, interact with neurons as a supportive partner supplying energy sources and growth factors. Astrocytes regulate the activity of neighboring neurons by releasing chemical transmitters (gliotransmitters). However, the precise role of gilotransmitters in regulating neuronal activity is still under debate. Here, we report that a subtle enhancement in the release of one gliotransmitter, ATP, affects synaptic potentiation from an analysis of mice containing an astrocyte‐selective (GFAP) mutation. We found that, relative to normal mice, weaker stimulation induced long‐term potentiation (LTP) in mutant mice, indicating that the threshold to induce LTP was lowered in the mutant. While excitatory transmission was normal in the mutant, inhibitory GABAergic transmission was suppressed. We found that a low concentration of adenosine selectively attenuated inhibitory neuronal activity and lowered the threshold to induce LTP in wild type mice. In comparison, adenosine A1 receptor antagonism reversed the lowered LTP threshold back to normal in the mutant mouse. We verified that adenosine levels in the cerebrospinal fluid of mutant mice were slightly elevated compared to wild type mice. This was apparently caused by an increase in ATP release from mutant astrocytes that could provide a source of augmented adenosine levels in the mutant. ATP is thought to suppress the excitability of neuronal circuits; however, a small increase in ATP release can result in a suppressed inhibitory tone and enhanced excitability of neuronal circuitry. These findings demonstrate that ATP released from astrocytes acts in a bidirectional fashion to regulate neuronal excitability depending on concentration. © 2012 Wiley Periodicals, Inc.